EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER ( NHT) DAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA PRESTASI BELAJAR MATEMATIKA DITINJAU DARI MOTIVASI BERPRESTASI - Yuzianah, Dita (Universitas Ahmad Dahlan, 2011)
The objectives of the research are to investigate: (1) the effectiveness of the cooperative learning model of NHT compared to that of the cooperative learning model of STAD, (2) the learning achievement in Mathematics learning of the students with the high, medium, and low achievement motivations, (3) the effectiveness of the cooperative learning model of NHT of the students with the high, medium and low achievement motivations, (4) the effectiveness of the cooperative learning model of STAD of the students with the high, medium, and low achievement motivations, and (5) the effectiveness of the cooperative learning models of NHT and STAD for each category of the achievement motivations.The research used a quasi-experimental research method. The population of the research was all of the students in Grade IV of 12 State Primary Schools in Belitang sub-district in the academic year of 2010/2011. The samples of the research were taken by using a stratified cluster random sampling technique, and were divided into two experimental groups. Experimental Group I consisted of 86 students of three schools, and Experimental Group II consisted of 73 students of 3 schools. The data of the research were gathered through documentation, questionnaire, and test. They were then analyzed by using a two-way analysis of variance with unequal cells. Prior to the analysis, the instruments were exposed to the pre-requisite tests of normality test and homogeneity test.The results of the research are as follows: (1) the learning achievement in Mathematics learning of the students taught with the cooperative learning model of NHT is the same as that of the students taught with the cooperative learning of STAD; (2) the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the medium achievement motivation, the learning achievement in Mathematics learning of the students with the medium achievement motivation is better than that of the students with the low achievement motivation, and the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the low achievement motivation; (3) in the cooperative learning model of NHT, the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the medium achievement motivation, the learning achievement in Mathematics learning of the students with the medium achievement motivation is better than that of the students with the low achievement motivation, and the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the low achievement motivation; (4) in the cooperative learning model of STAD, the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the medium achievement motivation, the learning achievement in Mathematics learning of the students with the medium achievement motivation is better than that of the students with the low achievement motivation, and the learning achievement in Mathematics learning of the students with the high achievement motivation is better than that of the students with the low achievement motivation; and (5) the students with the high, medium, and low achievement motivations taught with the cooperative learning model of NHT have the same learning achievement in Mathematics learning as those taught with the cooperative learning model of STAD.